Shedding light on net neutrality: The Brazilian case - Marcio Wohlers; Moacir Giansante; Antonio Carlos Bordeaux-Rego; Nathalia Foditsch (International Telecommunications Society (ITS), 2014)
The recently enacted 'Civil Rights Framework for the Internet' (Marco Civil), is a Law that has set the grounds for different Internet related rights in Brazil. Among its provisions are the ones related to network neutrality. Due to the importance of the topic, as well as its relevance for the Internet ecosystem, this paper aims at analyzing net neutrality as per established on Marco Civil. In order to do so, it utilizes the theory of Chris Marsden, who has classified neutrality into the "backward-looking" and 'forward-looking' models and also defends a co-regulatory institutional model. Moreover, this paper also draws insights from the recent debate over net neutrality United States, which are also re-evaluating it's regulatory approach to the topic.
Keywords: 330